PENGARUH STRATEGI PROMOSI MELALUI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO RIZKY STAMP LHOKSEUMAWE - Cut Auliana; Nanda Ameliany (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
This study aims to see the effect of promotional strategies on consumer purchasing decisions on the Rizky Lhokseumawe stamp. This research is a survey research. The population in this study were Followers on the Rizky Stamp Lhokseumawe online shop account, namely @onshoplhokseumawe, and the sample in this study were Followers on the Rizky Stamp Lhokseumawe online shop intagram account, @onshoplhokseumawe using the Slovin formula, a sample technique that uses a critical value or accuracy limit. of 0.1, so that the sample in the study was 100 respondents from a total population of 11,900 followers. The questionnaire trial consisted of validity testing using the Product Moment method and reliability testing using the Cronbach's Alpha method. This study uses simple regression analysis techniques with hypothesis testing using the SPSS 22 program. The results of this study indicate that the Promotion Strategy for Consumer Purchase Decisions at Rizky Stamp Lhokseumawe.